Lifetime modelling of high temperature corrosion processes proceedings of an EFC Workshop 2001 - Schütze, Michael; Quadakkers, W. J.; Nicholls, J. R. 1948- (Maney Pub., 2001)
The sections include papers on: alumina formers; iron oxide and chromia formers; composites and coatings; thermal barrier systems; and general lifetime prediction approaches.
Selected papers from a workshop held at DECHEMA, Frankfurt am Main, 22-23 February, 2001.
Keywords: Heat resistant alloys -- Congresses.; Corrosion resistant alloys -- Congresses.; Materials at high temperatures -- Congresses.; elektronické knihy; electronic books